Existence, Uniqueness, and Asymptotic Behavior for Nonlocal Parabolic Problems with Dominating Gradient Terms - Topp-Paredes, E (Society for Industrial and Applied Mathematics Publications, 2016)
In this paper we deal with the well-posedness of Dirichlet problems associated to nonlocal Hamilton-Jacobi parabolic equations in a bounded, smooth domain, in the case when the classical boundary condition may be lost. We address the problem for both coercive and noncoercive Hamiltonians: for coercive Hamiltonians, our results rely more on the regularity properties of the solutions, while noncoercive case are related to optimal control problems and the arguments are based on a careful study of the dynamics near the boundary of the domain. Comparison principles for bounded sub-and supersolutions are obtained in the context of viscosity solutions with generalized boundary conditions, and consequently we obtain the existence and uniqueness of solutions in C(Ω × [0,+∞)) by the application of Perron s method. Finally, we prove that the solution of these problems converges to the solutions of the associated stationary problem as t → +∞ under suitable assumptions on the data. © 2016 Society for Industrial and Applied Mathematics.